2005
DOI: 10.1002/mnfr.200400109
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and human health - beneficial or detrimental? - Mechanisms for effects of coffee consumption on different risk factors for cardiovascular disease and type 2 diabetes mellitus

Abstract: Coffee is probably the most frequently ingested beverage worldwide. Especially Scandinavia has a high prevalence of coffee-drinkers, and they traditionally make their coffee by boiling ground coffee beans and water. Because of its consumption in most countries in the world, it is interesting, from both a public and a scientific perspective, to discuss its potential benefits or adverse aspects in relation to especially two main health problems, namely cardiovascular disease and type 2 diabetes mellitus. Epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
172
1
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(187 citation statements)
references
References 103 publications
(97 reference statements)
3
172
1
11
Order By: Relevance
“…Another explanation could be residual confounding by unhealthy lifestyles in the categories of higher coffee consumption. In addition, it could be explained by higher intake of ingredients associated with increased risks of type 2 diabetes, such as kahweol and cafestol [31].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be residual confounding by unhealthy lifestyles in the categories of higher coffee consumption. In addition, it could be explained by higher intake of ingredients associated with increased risks of type 2 diabetes, such as kahweol and cafestol [31].…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine has been shown to exhibit several biological effects, such as increased fat oxidation and mobilization of glycogen in muscle, increased lipolysis and decreased body fat. 27 Further confirmation is required in large prospective studies, especially RCTs.…”
Section: Effect Of Coffee Consumption On Serum Lipids L Cai Et Almentioning
confidence: 99%
“…29 Coffee oils, including cafestol and kahweol, increase the synthesis of cholesterol by decreasing excretion of bile acids and neutral sterols. 27 The lipid-raising effects of coffee drinking pose a possible threat to coronary health. In general, case-control studies have found high-coffee intakes to be associated with significantly increased risk of CHD.…”
Section: Effect Of Coffee Consumption On Serum Lipids L Cai Et Almentioning
confidence: 99%
“…The name coffee is derived from the name of the province Keffa where shepherds from Abyssinia/Ethiopia discovered the coffee beans in the 6 th century [1]. Since then, coffee has become one of the most widely consumed beverages throughout the world [2] due to its pleasant taste [3], aroma [3], [4] stimulant effect [5] and health benefits [6].…”
Section: Introductionmentioning
confidence: 99%